MEMBANGUN CITRA DAN REPUTASI PENDIDIKAN ISLAM MELALUI STRATEGI MARKETING LEMBAGA PENDIDIKAN ISLAM - Supandi, Supandi; Abdul Khobir; Aini, Kurratul (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
Islamic education is an integral part of the identity of Muslims, therefore, an effective marketing strategy is needed to build progress and a strong image of the institution in society. This research aims to explore the marketing value contained in the Al-Qur'an and apply it in the context of Islamic education to strengthen the image and reputation of the progress of Islamic educational institutions. The research method uses a literature study approach with a focus on the Koran as the main source. The research stages include identifying relevant verses of the Koran, collecting in-depth Islamic literature, analyzing marketing values ​​in the Koran, as well as comparing them with modern marketing principles. The analysis results show that the Koran contains ethical values ​​such as honesty, trustworthiness, justice, and concern for consumers which can be adapted into Islamic education marketing strategies. The implication of this research is the preparation of marketing strategy recommendations based on Al-Qur'an values ​​to build a positive image and reputation for Islamic educational institutions. This study is expected to contribute to developing an understanding of the application of Al-Qur'an values ​​in the context of marketing Islamic education as well as providing practical guidance for decision-makers in utilizing the spiritual heritage of the Al-Qur'an for ethical and effective marketing purposes. The implications of this research are: 1) the importance of recommendations and testimonies, 2) teaching transparency and honesty, 3) service and quality, 4) community and social solidarity.